Do Thyroid Diseases during Pregnancy and Lactation Affect the Nutritional Composition of Human Milk? - Lopes, Fernanda de Oliveira; Soares, Fernanda Valente Mendes; Silva, Danielle Aparecida da; Moreira, Maria Elisabeth Lopes (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Objective To identify whether the effects of thyroid disease during pregnancy and lactation affect the nutritional composition of human milk.Methods Systematic review of the scientific literature using the Medical Literature Analysis and Retrieval System Online/MedLine databases to evaluate the association of thyroid diseases during pregnancy and lactation with the nutritional composition of human milk. There was no delimitation by period or by language, and the searches were completed in March 2019. The following descriptors were applied: human milk AND thyroid AND composition, using the preferred reporting items for systematic reviews and meta-analyses (PRISMA) protocol for data search, selection, and extraction. The flowchart proposed for bibliographic search resulted in 12 articles and, of these, four were selected.Results The articles elected for this review were published between 1976 and 2018. Two studies found significant differences in the nutritional composition of mothers' milk with hypothyroidism or overweight compared with the milk of those without hypothyroidism. Studies have shown that the presence of the disease led to changes in the nutritional composition of human milk, especially a higher concentration of human milk fat.Conclusion It is extremely important that these women have continuous nutritional follow-up to minimize the impact of these morbidities on the nutritional composition of human milk.
Keywords: human milk; macronutrients; composition; thyroid gland diseases; hypothyroidism